The Alpha-1A Adrenergic Receptor in the Rabbit Heart - Thomas, Jr., R. Croft; Cowley, Patrick M.; Singh, Abhishek; Myagmar, Bat-Erdene; Swigart, Philip M.; Baker, Anthony J.; Simpson, Paul C. (PLOS ONE, 2016)
The alpha-1A-adrenergic receptor (AR) subtype is associated with cardioprotective signaling in the mouse and human heart. The rabbit is useful for cardiac disease modeling, but data on the alpha-1A in the rabbit heart are limited. Our objective was to test for expression and function of the alpha-1A in rabbit heart. By quantitative real-time reverse transcription PCR (qPCR) on mRNA from ventricular myocardium of adult male New Zealand White rabbits, the alpha-1B was 99% of total alpha-1-AR mRNA, with <1% alpha-1A and alpha-1D, whereas alpha-1A mRNA was over 50% of total in brain and liver. Saturation radioligand binding identified 4 fmol total alpha-1-ARs per mg myocardial protein, with 17% alpha-1A by competition with the selective antagonist 5-methylurapidil. The alpha-1D was not detected by competition with BMY-7378, indicating that 83% of alpha-1-ARs were alpha-1B. In isolated left ventricle and right ventricle, the selective alpha-1A agonist A61603 stimulated a negative inotropic effect, versus a positive inotropic effect with the nonselective alpha-1-agonist phenylephrine and the beta-agonist isoproterenol. Blood pressure assay in conscious rabbits using an indwelling aortic telemeter showed that A61603 by bolus intravenous dosing increased mean arterial pressure by 20 mm Hg at 0.14 μg/kg, 10-fold lower than norepinephrine, and chronic A61603 infusion by iPRECIO programmable micro Infusion pump did not increase BP at 22 μg/kg/d. A myocardial slice model useful in human myocardium and an anthracycline cardiotoxicity model useful in mouse were both problematic in rabbit. We conclude that alpha-1A mRNA is very low in rabbit heart, but the receptor is present by binding and mediates a negative inotropic response. Expression and function of the alpha-1A in rabbit heart differ from mouse and human, but the vasopressor response is similar to mouse.